Hysterectomy: A leading cause of iatrogenic ureteric injuries in obstetric and gynaecologic surgeries - Dushyant, Rohit; Jain, Sheela (International Journal of Medical Research and Review, 2014)
Background: This study was done to share our surgical experience of iatrogenic ureteric injuries from obstetric and gynecological surgeries treated in the department of surgery Bundelkhand Medical College Sagar. Material and Method: A prospective study of 18 women who were treated for iatrogenic ureteric and bladder injuries secondary to obstetric and gynecological procedures in the department of surgery Bundelkhand Medical College, Sagar between 2010 & 2012. Results: In our study 18 cases were managed. 3 cases were treated for intra-operative injury by primary repair. Patients who ware diagnose later in course of disease were undergone Psoas hitch repair, had prolonged hospitalization with extra cost of treatment. Conclusion: Alhough ureteric injury is quite rare in obstetric & gynecological surgery but it is still a reality, to avoid it high degree of suspicion and careful tissue dissection is required. Intra-operative diagnosis had an excellent result but late diagnosis was associated with high morbidity.